ESENSI AGAMA DALAM KONFLIK SOSIAL DI KABUPATEN POSO MENGGUNAKAN TEORI KARL MARX: SEBUAH LITERATUR REVIEW [THE ESSENCE OF RELIGION IN SOCIAL CONFLICT AT POSO REGENCY USING THE THEORY OF KARL MARX: A LITERATURE REVIEW] - Sulhan, M.; Januri, Muhammad Rizal (Acta Islamica Counsenesia: Counselling Research and Applications, 2022)
This paper aims to describe the factors behind the conflict that occurred in Poso Regency through analysis of Karl Marx’s theory of conflict and the function of religion as a measure to reduce conflict. In this study, the writing used a qualitative approach and literature review. The results of this study describe that the conflict in Poso Regency is a series of cases that have occurred since 1998 and peaked in 2001. The background of the conflict is in accordance with the assumptions used by Marx: First, using economic determinism, namely by seeing that economic factors are the basic things in structural changes to society. Second, historical determinism, namely the structural change of society through three stages: thesis (affirmation), anti-thesis (negation), and synthesis (reconciliation of opposites). Meanwhile, efforts to reduce religion are based on the function of religion, patterned on the existence of religion in the community, not only as a system of beliefs and beliefs, but religion has several functions, both directly related and in direct contact with the social life of the community, which provide solutions to problems, rules and laws, source of unity, kindness, and glue the relationship between individuals.